2020
DOI: 10.3390/cancers12030753
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling for Predictors of Radiosensitivity in Patients with Breast or Head-and-Neck Cancer

Abstract: Nearly half of all cancers are treated with radiotherapy alone or in combination with other treatments, where damage to normal tissues is a limiting factor for the treatment. Radiotherapy-induced adverse health effects, mostly of importance for cancer patients with long-term survival, may appear during or long time after finishing radiotherapy and depend on the patient’s radiosensitivity. Currently, there is no assay available that can reliably predict the individual’s response to radiotherapy. We profiled two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 73 publications
(97 reference statements)
1
13
0
Order By: Relevance
“…Drobin et al reported the correlation and possible mechanism of VEGFA rs69947 with breast cancer and HNSCC radiotherapy sensitivity. The authors proposed that this SNP may affect protein expression, which would impact biological processes such as blood vessel growth, inflammatory cell infiltration, the immune response, DNA repair, oxidative stress and hypoxia (66). These changes may underlie the differences in correlation and sensitivity among patients.…”
Section: Discussionmentioning
confidence: 99%
“…Drobin et al reported the correlation and possible mechanism of VEGFA rs69947 with breast cancer and HNSCC radiotherapy sensitivity. The authors proposed that this SNP may affect protein expression, which would impact biological processes such as blood vessel growth, inflammatory cell infiltration, the immune response, DNA repair, oxidative stress and hypoxia (66). These changes may underlie the differences in correlation and sensitivity among patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, future objective studies in the field of RID research should also reflect patients’ genetic, epigenetic, and molecular profiles, since several promising relationships of tissue sensitivity towards radiotherapy have been described. Even though this kind of research is still in its infancy, we expect it to provide further clinically relevant insights into risk factors for radiotherapy-induced side effects [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have generated an RSS base on the intrinsic radiosensitivity in BRCA by the integration of post-radiation clonogenic survival data with gene expression data [11,[24][25][26]. To demonstrate whether immune infiltration level has predictive ability for RT outcomes, we developed a Radiosensitivity Signature (RSS) in BRCA ( Figure 5).…”
Section: Brca Radiosensitivity Signature Based On Immune Infiltrationmentioning
confidence: 99%
“…Each picture corresponds to a different type of cancer BRCA (B), CESC (C-F), GBM(G), HNSC (H, I), LGG (J), THCA (K-P).2.1.4. BRCA radiosensitivity signature based on immune infiltrationPrevious studies have generated an RSS base on the intrinsic radiosensitivity in BRCA by the integration of post-radiation clonogenic survival data with gene expression data[11,[24][25][26]. To…”
mentioning
confidence: 99%